MODEL MESIN INFERENSI PADA SISTEM PAKAR DENGAN LOGIKA SAMAR (Model of Inference Engine in Expert Systems Using Fuzzy Logic) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Farmasi UGM, 2000)
ABSTRACT Expert systems have been intensively developed in various applications to solve problems. The advantage of expert systems depend highly on the accuracy of setting up the knowledge base and its rules. Therefore, model of inference engine to manage of uncertainties is needed. There are several popular model of the inference engine to manage uncertainties, such as probability theory, Demster-Shafer theory, and possibility theory. Model of inference engine for reasoning with uncertainties in expert systems using fuzzy logic was discussed. Rules were given along with membership functions. The Model of inference engine was used to conduct analysis by combining several interpretations of implications, inference methods, and several operators. The final result of this analysis was a conclusion with some degree of truthfulness.